2006
DOI: 10.1542/peds.2005-2742
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin K Prophylaxis for Preterm Infants: A Randomized, Controlled Trial of 3 Regimens

Abstract: Vitamin K1 prophylaxis with 0.2 mg administered intramuscularly maintained adequate vitamin K status of preterm infants until a median age of 25 postnatal days and did not cause early vitamin K1 2,3-epoxide accumulation. In contrast, 0.2 mg administered intravenously and 0.5 mg administered intramuscularly led to vitamin K1 2,3-epoxide accumulation, possibly indicating overload of the immature liver. To protect against late vitamin K1 deficiency bleeding, breastfed preterm infants given a 0.2-mg dose of prophy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
81
2
8

Year Published

2007
2007
2018
2018

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(93 citation statements)
references
References 42 publications
(46 reference statements)
1
81
2
8
Order By: Relevance
“…However, it does not discount that low urinary output may also reflect an immaturity of the enzymic pathway leading to vitamin K catabolism. Despite the low liver stores at birth, detectable circulatory levels of PIVKA-II are present only in a minority of newborns (6,8,20). PIVKA-II was undetectable in all preterm infants in this study showed that their vitamin K status was sufficient for the efficient functional ␥-carboxylation of hepatic coagulation factors.…”
Section: Ga Median (Range)mentioning
confidence: 54%
See 3 more Smart Citations
“…However, it does not discount that low urinary output may also reflect an immaturity of the enzymic pathway leading to vitamin K catabolism. Despite the low liver stores at birth, detectable circulatory levels of PIVKA-II are present only in a minority of newborns (6,8,20). PIVKA-II was undetectable in all preterm infants in this study showed that their vitamin K status was sufficient for the efficient functional ␥-carboxylation of hepatic coagulation factors.…”
Section: Ga Median (Range)mentioning
confidence: 54%
“…This pattern may indicate saturation of a component(s) of the -and ␤-oxidative enzyme system that carries out degradative side chain shortening of vitamin K before excretion (18,19). The likelihood that some preterm infants are unable to efficiently metabolize current prophylactic doses of vitamin K given at birth is supported by the finding that many preterms in this trial still had grossly elevated circulatory levels of K 1 on the fifth day of life that reached concentrations to several 100-fold higher than endogenous concentrations in healthy adults (20). These finding are consistent with previous reports (11,12).…”
Section: Ga Median (Range)mentioning
confidence: 74%
See 2 more Smart Citations
“…Health care professionals should promote awareness among families of the risk of late VKDB associated with inadequate vitamin K prophylaxis from current oral dosage regimens, particularly for newborns who are breastfed exclusively 1,4 .…”
Section: American Academy Of Paediatrics 2003mentioning
confidence: 99%